2013
DOI: 10.1007/s11136-013-0606-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of influenza-like illness in young children on their parents: a quality of life survey

Abstract: Parents had significantly lower QoL while their child had ILI, compared with before ILI and with parents of children without ILI. The public health impact of ILI in children on the QoL in families is far from negligible. QoL measurement can complement economic evaluation of ILI disease burden and provide a more complete picture of impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Additionally, benefits may also include contraction in absenteeism due to the need for parents to take time of work to care for sick children, 46,47 and reduced pressure on health care services during seasonal peak in influenza activity. 48,49 Nevertheless, despite previous assumptions, only USA and Canada among large developed countries, and some rare exceptions in Europe such as Finland, Latvia and United Kingdom, actually recommend the influenza vaccination of healthy children providing the vaccine free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, benefits may also include contraction in absenteeism due to the need for parents to take time of work to care for sick children, 46,47 and reduced pressure on health care services during seasonal peak in influenza activity. 48,49 Nevertheless, despite previous assumptions, only USA and Canada among large developed countries, and some rare exceptions in Europe such as Finland, Latvia and United Kingdom, actually recommend the influenza vaccination of healthy children providing the vaccine free of charge.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian study showed that a case of community managed influenza infection in preschool‐aged children had a mean cost of $904 (2003 AUD), and caused an average of one medically attended visit per illness . In addition, the 2010 PIVOT cohort study found that an average of 13 hours of work were lost by carers of sick preschool‐aged children per ILI and that ILI in children resulted in a significant negative impact on the quality of life in parents due to disruptions of normal life routine, social isolation and stress coping with the sick child . Costs were similar regardless of whether infections were due to influenza or other respiratory viruses .…”
Section: Discussionmentioning
confidence: 99%
“…PIVOT 2011 collected information on clinical outcomes after vaccination as well as economic and psychosocial impacts after ILI in both study arms, similar to methodology for PIVOT 2010 . This paper reports the clinical outcomes, safety, and analysis of VE.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, reduced social activities decrease the quality of life of parents when dealing with sick children (Chow et al, 2014). In this study, social activity was measured as the number of days of social activity for two members of the household.…”
Section: Individual and Household Characteristicsmentioning
confidence: 99%